THE INFLUENCE OF PROFITABILITY ON STOCK PRICES - Wulandari, Aprilia; Nurlaela, Siti; Wijayanti, Anita (Universitas Tidar, 2024)
This study aims to test and examine how stock prices are affected by return on equity, net profit margin, earnings per share, and return on assets. For the period between 2020 and 2023, 55 food and beverage firms that were listed on the Indonesia Stock Exchange (IDX) were examined in this study. Purposive sampling methods based on predetermined criteria were utilized in the study. There are 21 firms with 84 data observations made up the study's sample. The analysis used in this study is multiple linear regression. The study's findings show that even though earnings per share and return on assets positively impact stock prices, return on equity has a negative effect on stock prices. However, stock prices are unaffected by the net profit margin.